2018
DOI: 10.1088/2058-6272/aadc05
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on upstream and downstream discharges in airflows

Abstract: Dielectric barrier discharge has widely used in airflow control, ignition and combustion, and other applications; the influence of airflow on dielectric barrier discharge is of extensive concern. Previous studies demonstrate that the discharge becomes more uniform and the discharge intensity decreases with increasing of airflow velocity. In this study, we adopt a discharge cell construction with upstream and downstream structure and study the discharge states and intensities. The experimental results demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Like other plasmas [41], high-energy excited particles produced by PMA cannot exist for a long time. These particles will collide with neutral gas molecules to form metastable particles with higher stability.…”
Section: Productmentioning
confidence: 97%
“…Like other plasmas [41], high-energy excited particles produced by PMA cannot exist for a long time. These particles will collide with neutral gas molecules to form metastable particles with higher stability.…”
Section: Productmentioning
confidence: 97%
“…Firstly, the 'edge effect' is considered to be the main reason for this phenomenon. Secondly, the airflow significantly changes the distribution of space ions, and the residual space ions at the inlet of the airflow move to the downstream region under the drag force [8,47]. Therefore, the space ion density at the outlet of the airflow is slightly higher than that at the inlet before next discharge, which causes the discharge to ignite preferentially at the outlet, resulting in a larger positive charge density at the outlet.…”
Section: Effect Of the Airflow Velocity On The Uniformity Of The Surf...mentioning
confidence: 99%
“…Recently, a large number of investigations showed that introducing the airflow to the discharge gap promised to be a good alternative candidate to form uniform discharge [7,8]. The effect of airflow on the uniformity of atmosphericpressure air NPDBD was studied by many researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Once the excited particles rise to the metastable state, they cannot spontaneously jump to the ground state, so the metastable particles have a relatively long lifetime. According to [38][39][40], N 2 electronically excited state particles are generated as the main type of excited particles, with a relatively high concentration in the discharge area. Considering different excited states of N 2 molecules, N 2 (A) can be called a metastable particle with a lifetime of about milliseconds; N 2 (B) is always quickly quenched with a muchshorter lifetime of about tens of microseconds.…”
Section: Mechanism Of the Hysteresis Characteristicsmentioning
confidence: 99%